Competing Combinatorial Auctions - Thomas Kittsteiner; Marion Ott; Richard Steinberg (Information Systems Research, 2021)
We investigate whether revenue-maximizing auctioneers selling heterogeneous items will allow for combinatorial bidding in the presence of auctioneer competition. We compare the choice of auction format by two competing auctioneers with that of a single auctioneer. Bidders are heterogeneous in their demands, with some having synergies for items. We find that, even if a single auctioneer offers a combinatorial auction, competing auctioneers in a comparable setting will not. Instead, the competing auctioneers will segment the market by restricting allowable package bids in order to increase competition between bidders. This shows that it might not be advantageous for an online market platform to offer combinatorial auctions as a design option to competing auctioneers.
Keywords: D44; C72; D82; 330; Competing auctioneers; Combinatorial auction; Electronic marketplace; VCG mechanism